An Overview of the Sociological and Environmental Factors Influencing Eating Food Behavior in Canada - Marcone, Massimo F.; Madan, Pavneesh; Grodzinski, Bernard (Frontiers in Nutrition, 2020)
The food eating behavior of individuals are mainly determined by various factors, such as economic environment, the social environment, and the physical environment. This review evaluates the social economic ecosystem of Canadians with focus on food insecurity and important factors affecting food insecurity. Additionally, this review extensively discusses various socio-environmental factors affecting eating behavior of the general public within Canada including the development and implementation of national policies. A research gap shows that there is a significant need to address the development and implementation of policies in the food and nutrition environment. Lastly, we investigate the role in which biotechnology plays in improving food security and addresses the significant impact biotechnology has contributed towards on agriculture and the food market. Overall this review provides significant contribution towards understanding the social economic environment and eating behavior of people living in Canada.